Bridging the performance gap: Interdisciplinary collaboration with sports dietitians - Potter, S.; Boyd, J. M. (Strength and Conditioning Journal, 2017)
Athletes and coaches are aware of the importance of adequate nutrition for athletic performance; however, most lack adequate nutrition knowledge. Athletes express interest in learning more about nutrition for performance but consistently consult sources with little nutrition knowledge. Sports dietitians can assist athletes in meeting nutrition needs but are often underutilized for athletic performance. This article discusses the current needs of athletes, differences in nutrition titles, current state of sports dietitians, and the benefit of using a sports dietitian.